Simple and efficient heterologous expression of necrosis‐inducing effectors using the model plant Nicotiana benthamiana. (23rd August 2021) - Dagvadorj, Bayantes; Solomon, Peter S.
Abstract: Plant fungal pathogens cause devastating diseases on cereal plants and threaten global food security. During infection, these pathogens secrete proteinaceous effectors that promote disease. Some of these effectors from necrotrophic plant pathogens induce a cell death response (necrosis), which facilitates pathogen growth in planta . Characterization of these effectors typically requires heterologous expression, and microbial expression systems such as bacteria and yeast are the predominantly used. However, microbial expression systems often require optimization for any given effector and are, in general, not suitable for effectors involving cysteine bridges and posttranslational modifications for activity. Here, we describe a simple and efficient method for expressing such effectors in the model plant Nicotiana benthamiana . Briefly, an effector protein is transiently expressed and secreted into the apoplast of N. benthamiana by Agrobacterium‐mediated infiltration. Two to three days subsequent to agroinfiltration, the apoplast from the infiltrated leaves is extracted and can be directly used for phenotyping on host plants. The efficacy of this approach was demonstrated by expressing the ToxA, Tox3, and Tox1 necrosis‐inducing effectors from Parastagonospora nodorum . All three effectors produced in N. benthamiana were capable of inducing necrosis in wheat lines, and two of three showed visible bands on Coomassie‐stained gel. These data suggest that N. benthamiana –agroinfiltration system is a feasible tool to obtain fungal effectors, especially those that require disulfide bonds and posttranslational modifications. Furthermore, due to the low number of proteins typically observed in the apoplast (compared with intracellular), this simple and high‐throughput approach circumvents the requirement to lyse cells and further purifies the target proteins that are required in other heterologous systems. Because of its simplicity and potential for high‐throughput, this method is highly amenable to the phenotyping of candidate protein effectors on host plants.